Negation, expectation and ideology in written texts : a textual and communicative perspective - Nahajec, Lisa (Linguistic approaches to literature ;, 2021)
"During an election campaign in 2008, Ken Livingstone said to a newspaper reporter "this election is not a joke". By doing so, he introduced an expectation into the discourse that someone does, in fact, think it is a joke. This book explores how it is that saying what is not the case communicates something about what is. Bringing together a focus on text with cognitive and pragmatic approaches, a case is made for an application of linguistic negation as a tool of analysis. This tool is used to explore the ideological implications of projecting or reflecting readerly expectations. This book contributes to the growing field of Critical stylistics and aims to add to the range of stylistic insights which anchor the analysis of discourse to a consideration of the nuances of language choice"--